Mapping of transgenic alleles in soybean using a nanopore-based sequencing strategy. (30th April 2019) - Li, Shengjun; Jia, Shangang; Hou, Lili; Nguyen, Hanh; Sato, Shirley; Holding, David; Cahoon, Edgar; Zhang, Chi; Clemente, Tom; Yu, Bin
Abstract : A high-throughput, convenient, reliable, and cost-efficient sequencing method to identify transgene insertion positions in the genome is described. Abstract: Transgenic technology was developed to introduce transgenes into various organisms to validate gene function and add genetic variations >40 years ago. However, the identification of the transgene insertion position is still challenging in organisms with complex genomes. Here, we report a nanopore-based method to map the insertion position of a Ds transposable element originating in maize in the soybean genome. In this method, an oligo probe is used to capture the DNA fragments containing the Ds element from pooled DNA samples of transgenic soybean plants. The Ds element-enriched DNAs are then sequenced using the MinION-based platform of Nanopore. This method allowed us to rapidly map the Ds insertion positions in 51 transgenic soybean lines through a single sequencing run. This strategy is high throughput, convenient, reliable, and cost-efficient. The transgenic allele mapping protocol can be easily translated to other eukaryotes with complex genomes.